2021
DOI: 10.1155/2021/8019385
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of Nursing Defect Management Evaluation and Deep Learning in Nursing Process Reengineering Optimization

Abstract: It was to explore the application of nursing defect management evaluation and deep learning in nursing process reengineering optimization. This study first selects the root cause analysis method to analyse the nursing defect management, then realizes the classification of data features according to the convolution neural network (CNN) in deep learning (DL) and uses the constructed training set and verification set to obtain the required plates and feature extraction. Based on statistical analysis and data mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Another dimension of the Persian version of the NCQS was the nursing process. The application of the nursing process has a significant role in the development of the QNC (Liu & Liu, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another dimension of the Persian version of the NCQS was the nursing process. The application of the nursing process has a significant role in the development of the QNC (Liu & Liu, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another dimension of the Persian version of the NCQS was the nursing process. The application of the nursing process has a significant role in the development of the QNC (Liu & Liu, 2021). However, it has been demonstrated that many nurses, particularly, in developing countries scarcely use the nursing process in care provision (Silva et al, 2021; Zeleke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 18 Process reengineering refers to the process of rebuilding and optimizing the original workflow using modern management means. 25 In recent years, the application of process reengineering has produced a series of changes in nursing management; 18 However, the process that conforms to reality and meets the needs should be formulated according to the specific situation. 26 Since 2020, the number of deaths from infection worldwide has been increasing dramatically, and countries have made changes accordingly, including optimizing healthcare systems and developing crisis management plans to improve the resilience of healthcare systems that have struggled to adapt as well as to continuously optimize crisis management strategies in response to subsequent emergencies, making dynamic system changes.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%